Activation of Notch3 promotes pulmonary arterial smooth muscle cells proliferation via Hes1/p27Kip1 signaling pathway - Song, Yang (FEBS Open Bio, 2015)
Activation of the Notch3 cascade is involved in the development of pulmonary arterial hypertension by stimulating the proliferation of vascular smooth muscle cells. However, the detailed molecular mechanisms underlying this effect are still unclear. The present study aims to address this issue. We demonstrated that over-expression of intracellular domain of the Notch3 receptor (NICD3) by adenovirus transfection dramatically induced proliferation of primary cultured pulmonary artery smooth muscle cells. This was accompanied with up-regulation of Hes1 protein and down-regulation of p27Kip1 protein. More importantly, we observed that prior silencing of Hes1 with siRNA blocked NICD3 over-expression-induced p27Kip1 reduction and cell proliferation. The present study suggests that Hes1 lies downstream of NICD3 and particularly mediates Notch3 signaling-induced proliferation of pulmonary arterial smooth muscle cells by down-regulation of p27Kip1 expression.